Leveraging Psychological Capital and Leadership Autonomy Support to Enhance Innovative Behavior: Mediating Role of Individual Creativity in the Hospitality Sector - Nur Cahyadi; Abdul Kadir Alamudi; Mega Aprillia Pratamasari; Zaki Nur Hamam (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: Hospitality-related services, such as accommodation, food and beverage, and travel, are an important part of the global economy. This industry greatly helps economic growth, creates jobs, and increases tourism in many countries, including Indonesia, in addition to serving customers. Hence, current research seek to investigate the impact of psychological capital, leadership autonomy support on innovative behavior. The researchers also observed how individual creativity functions as a mediator. According to Self-Determination Theory (SDT), psychological capital, individual creativity, and innovative behavior are influenced by employees’ opinions about leaders as supporters of autonomy. Methodology: This study involved 255 respondents from hotel employees. The sampling method used was the chance sampling method. Then, the collected data were analyzed using Partial Least Squares (PLS). Findings: The results of the analysis showed that all hypotheses studied influenced creative behavior, and employees would tend to have the intention to work with strong autonomy support. In addition, factors such as creativity, leadership autonomy, and psychology also played a significant role in encouraging employee innovative behavior. Implications/Novel Contribution: This research supports the theory of the relationship between psychological capital and innovation, by showing that individuals who have high psychological capital tend to be more creative and more innovative. Thus, extending the body of literature in given field and brings key policy take aways for the hospitality industry managers, scholars and policy makers.